Sobrevivência de implantes dentários em pacientes com câncer de cabeça e pescoço irradiado em comparação com pacientes não irradiados: overview de revisões sistemáticas - Maria Cândida Dourado Pacheco (2024)
There is a growing demand for oral rehabilitation in patients undergoing radiation to treat head and neck cancer. Although radiotherapy appears to negatively affect implanted oral rehabilitation, the evidence provided by previous systematic reviews in the area remains controversial. Therefore, this overview aimed to evaluate the survival of dental implants installed before and/or after radiotherapy in patients with head and neck cancer compared to those not irradiated. The study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines. The electronic databases Pubmed/MEDLINE, Cochrane Library, Embase, Web of Science and Google Scholar were consulted, without language restrictions and without date limits, to identify relevant articles published up to February 2024. A manual search was carried out in a list of references in all included studies. The percentage of dental implant survival was the primary outcome. Methodological quality was assessed using the A MeaSurement Tool to Assess Systematic Reviews 2 (AMSTAR 2). The search for studies, data extraction and assessment of methodological quality were carried out in duplicate by two reviewers independently. The protocol for this review was registered with PROSPERO (CRD42023406059). The initial search resulted in 1,811 articles and after applying the eligibility criteria, 11 systematic reviews were selected. 73,674 implants installed in 16,193 patients were evaluated. Quantitative analysis showed that 2,674 failures occurred in 14,471 implants installed in irradiated bone and 1,825 failures in 34,092 implants in non-irradiated bone. The survival percentage was 81.52% for irradiated implants and 94.64% for non-irradiated implants. A significant difference in survival in favor of implants in non-irradiated bone is supported by 11 meta-analyses. The included systematic reviews were considered to be of critically low methodological quality. The research showed that implants installed in patients undergoing radiotherapy had a higher percentage of failures, despite the critically low methodological quality found in systematic reviews. New clinical studies with better research design must be carried out.